(untitled) (Czech Journal of International Relations, 2020)
The article examines the processes of memory securitization in the Russian Federation and Latvia during the coronavirus crisis. The key factor that allowed the authors to make such a statement about the problem was the temporary coincidence of the pandemic with the 75th anniversary of the final defeat of Nazi Germany and the so-called Victory Day. As a theoretical basis for the study, we use the constructivist understanding of security in order to study, with specific examples, how the threat in the form of a pandemic became a frame for securitization of memory. The authors identify the peculiarities of the articulating of security problems by political elites in two states with different memory regimes framed by the pandemic as an external factor.